Non-Functional Trace Amine-Associated Receptor 1 Variants in Patients With Mental Disorders - Rutigliano, Grazia; Bräunig, Julia; Del Grande, Claudia; Carnicelli, Vittoria; Masci, Isabella; Merlino, Sergio; Kleinau, Gunnar; Tessieri, Luca; Pardossi, Simone; Paisdzior, Sarah; Dell’Osso, Liliana; Biebermann, Heike; et al. (Frontiers in Pharmacology, 2019)
Background: The G protein–coupled receptor (GPCR) trace amine-associated receptor 1 (TAAR1) is expressed across brain areas involved in emotions, reward and cognition, and modulates monoaminergic and glutamatergic neurotransmissions. TAAR1 is stimulated with nanomolar affinity by 3-iodothyronamine (T1AM), an endogenous messenger considered a novel branch of thyroid hormone signaling. The human gene for TAAR1 maps to locus 6q23, within a region associated with major mental disorders. Materials and Methods: We screened a cohort of patients with major mental disorders (n = 104) and a group of healthy controls (n = 130) for TAAR1 variants. HEK293 cells were transiently transfected with: i) wild-type TAAR1 and ii) mutated TAAR1, either in homozygous or heterozygous state. Cell surface expression and Gs/adenylyl cyclase activation upon administration of β-phenylethylamine (PEA), T1AM, and RO5166017, were assessed. Results: We detected 13 missense variants in TAAR1 coding region, with a significant enrichment in patients as compared to healthy controls (11 vs. 1, 1 variant in both groups, p < 0.01). In silico analysis identified four dysfunctional variants, all in patients. Three of these—R23C, Y131C, and C263R—were functionally characterized. In cells co-transfected with wild-type and mutated TAAR1, we observed a significant reduction of cell surface expression. In heterozygosity, the three TAAR1 variants substantially dampened Gs signaling in response to PEA, and, more robustly, to T1AM. Co-stimulation with PEA and RO5166017 did not yield any improvement in Gs signaling. R23C, Y131C, and C263R are rare in the general population and map in functionally important highly conserved positions across TAAR1 orthologous and paralogous genes. Conclusions: Our findings suggest that disruptions of TAAR1 activity may be relevant to the pathophysiology of mental disorders, thereby providing a promising target for novel psychopharmacological interventions.